2012
DOI: 10.1371/journal.pone.0034326
|View full text |Cite
|
Sign up to set email alerts
|

Altered Thymic Function during Interferon Therapy in HCV-Infected Patients

Abstract: Interferon alpha (IFNα) therapy, despite good efficacy in curing HCV infection, leads to major side effects, in particular inducement of a strong peripheral T-cell lymphocytopenia. We here analyze the early consequences of IFNα therapy on both thymic function and peripheral T-cell homeostasis in patients in the acute or chronic phase of HCV-infection as well as in HIV/HCV co-infected patients. The evolution of T-cell subsets and T-cell homeostasis were estimated by flow cytometry while thymic function was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In contrast, interferon-a does not seem to affect the proportion of T cells expressing IL-7Ra. Thus, we found no effect of PEG/ R AE 1.PI treatment on the proportion of IL-7Ra+ T cells and a decrease in the proportion of IL-7Ra+ T cells post SVR which is in agreement with previous studies (23,25). Furthermore, the reduced proportion of IL-7Ra+ T cells post SVR is consistent with our previous study demonstrating higher proportions of IL-7Ra+ CD4+ T cells in chronic HCV patients with fibrosis compared to healthy controls (16).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, interferon-a does not seem to affect the proportion of T cells expressing IL-7Ra. Thus, we found no effect of PEG/ R AE 1.PI treatment on the proportion of IL-7Ra+ T cells and a decrease in the proportion of IL-7Ra+ T cells post SVR which is in agreement with previous studies (23,25). Furthermore, the reduced proportion of IL-7Ra+ T cells post SVR is consistent with our previous study demonstrating higher proportions of IL-7Ra+ CD4+ T cells in chronic HCV patients with fibrosis compared to healthy controls (16).…”
Section: Discussionsupporting
confidence: 93%
“…Interferon-a modulates both innate and adaptive immune responses (20,21), and interferon-a is related to a variety of adverse events including anemia, neutropenia, and lymphopenia (22). The mechanisms causing lymphopenia are complex and not completely understood, but interferon-a affects both hematopoiesis at an early stage and lymphoid differentiation at a later stage including direct impairment of thymic output (23,24). Furthermore, decreased interleukin (IL)-7 plasma levels has been documented during interferon-a treatment (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have underscored the role of type I interferons in thymic development and T-cell selection (33). Moreover, it was shown that fetal thymocytes are susceptible to viral infections (34), and IFNα treatment in patients with HCV infection is associated with inhibition of intrathymic precursor Tcell proliferation (35). Thus, our data support the concept that genetic-epigenetic regulation of intrathymic self-antigen expression (e.g., TSHR) is key to self-tolerance, and that alterations in these mechanisms can decrease autoantigen expression in the thymus, leading to escape of self-reactive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Early ID was seen during or within 6 weeks of discontinuation of PEG-IFN/RBV therapy and often resulted in premature termination of PEG-IFN/RBV; it may reflect unmasking or exacerbation of autoimmune hepatitis by PEG-IFN, a phenomenon that is also seen in the non-transplant setting [2327]. Late ID was seen ≥6 months after discontinuation of PEG-IFN/RBV therapy with no other precipitating cause.…”
Section: Discussionmentioning
confidence: 99%